Original paper Psychosocial Functioning Questionnaire for Patients with Low Back Pain: development and psychometric properties - Konrad Janowski (Archives of Medical Science, 2005)
Background: Low back pain (LBP) is a common chronic disease causing pain and severe imitations in mobility. Apart from physical impairment, LBP also affects psychosocial functioning in such domains as interpersonal relationships, emotions or everyday-living activities. In Poland there is a relative lack of tools evaluating the psychosocial functional status in patients with LBP. Objective: The objective of the study was to develop and test psychometric properties of a new instrument measuring dimensions of psychosocial functioning in patients with LBP – Psychosocial Functioning Questionnaire (PFQ) for Patients with Low Back Pain. Subjects and methods: 100 subjects with LBP took part in the study and completed the initial version of PFQ. A subgroup of 30 random patients was tested with PFQ again after 72 hours. Results: Factor analysis revealed five factors explaining 43% of the total variance. After deleting items with inadequate psychometric properties, the factors were taken to construct five subscales of PFQ: 1. Distress in interpersonal context; 2. Limitations in everyday functioning; 3. Acceptance of life with the disease; 4. Depressive complaints; and 5. Sense of being disabled. Intercorrelations between the subscales ranged from 0.36 to 0.69 and showed an expected pattern. Internal consistency coefficients for the subscales ranged from 0.86 to 0.89, and test-retest correlations ranged from 0.80 to 0.90. None of the subscales showed statistically significant associations with such sociodemographic variables as age, gender, marital status, place of residence or duration of the disease. Scores of one subscale – Acceptance of life with the disease – differed significantly in subgroups with various educational levels. Conclusions: PFQ is a reliable questionnaire which could be a useful instrument in evaluation of psychosocial functioning in patients with LBP. Further research is needed to assess other psychometric properties of PFQ.